Enhanced Functional Connectivity Within Executive Function Network in Remitted or Partially Remitted MDD Patients - Wang, Yuchen; Zhang, Aixia; Yang, Chunxia; Li, Gaizhi; Sun, Ning; Liu, Penghong; Wang, Yanfang; Zhang, Kerang (Frontiers in Psychiatry, 2021)
Background: Impaired executive function (EF) is associated with a range of typical clinical characteristics and psychosocial dysfunction in major depressive disorder (MDD). However, because of the lack of objective cognitive tests, inconsistencies in research results, and improvement in patients’ subjective experience, few clinicians are concerned with the persistent impairment of EF in euthymia. The study makes a further investigation for EF in remitted and partially remitted MDD patients via multiple EF tests and fMRI, so as to explore the executive function of patients in euthymia. Methods: We recruited 19 MDD patients and 17 age-, gender-, and education-matched healthy controls (HCs). All participants completed EF tests and fMRI scanning. Bilateral dorsolateral prefrontal cortex (dlPFC) regions were selected as the region of interests (ROIs) to conduct seed-based functional connectivity (FC). We conducted fractional amplitude of low-frequency fluctuations (fALFF) analysis for all ROIs and whole brain. Results: All MDD patients were in remission or partial remission, and they were comparable with HCs on all the EF tests.MDD group showed increased positive FC between left dlPFC and cerebellar Crus I, right dlPFC and supramarginal gyrus after 8-week treatment, even taking residual depressive symptoms into account. We did not find group difference of fALFF value. Conclusion: MDD patients persisted with EF impairment despite the remission or partially remission of depressive symptoms. Clinicians should focus on residual cognitive symptoms, which may contribute to maximize the efficacy of routine therapy.